FADING OF THE CONTINUUM OF NOISE STORMS IN THE DECAMETER RANGE RELATED TO CME - Isaeva, E. A. (Одеські астрономічні публікації, 2019)
In this paper, we studied the incompre- hensible fading of a continuum of noise storms and type IV continual bursts in the decameter range, coinciding in time with coronal mass ejections (CMEs) for solar proton events (SPE). A comparative analysis showed that about 60% of the CMEs are accompanied by the fading of the continuum of noise storms and type IV continual bursts in the range of 25-30 MHz. It is shown that the fading of the continuum of a noise storm associated with a CME is distinguished by the intensity and duration of fading, as well as the width of the fading band and the frequency at which the maximum fading depth is observed. Moreover, detailed studies have shown that, against the background of a general decline in the radiation flux, a fine temporal structure at adjacent fre- quencies remains. This may indicate that the radiation is shielded by an external region in the path of radiation prop- agation. It can be a cold and dense cloud of the CME itself or absorption in the ionosphere. Absorption at low frequen- cies in the Earth's ionosphere is quite possible, since the x- ray and ultraviolet radiation of the flare can cause addi- tional short-term ionization. In this regard, studies have been conducted on the relationship of the fading of the con- tinuum of noise storms with x-ray flares. A comparative analysis showed that there is a fairly strong relationship be- tween the integral flux and the effective duration of x-ray flares with the integral flux and the effective duration of the decrease in the continuum of noise storms, respectively. Moreover, the relationship between the effective durations is slightly higher, where the correlation coefficient between the studied values is ≈ 0.71. It was also shown that short- term impulse fading is associated with impulse x-ray flares, and long-term with gradual long-term x-ray flares. It was noted above that absorption can also occur in the body of the CME itself, therefore, the relationship between the pa- rameters for lowering the continuum of noise storms at a given frequency and the speed of the CME was investi- gated. A comparative analysis showed that there is a fairly strong relationship between the maximum fading depth and the CME speed, where the correlation coefficient between the studied values is ≈ 0.65.